Brazilian Consensus for the Treatment of Multiple Sclerosis: Brazilian Academy of Neurology and Brazilian Committee on Treatment and Research in Multiple Sclerosis - Marques, Vanessa Daccach; Passos, Giordani Rodrigues dos; Mendes, Maria Fernanda; Callegaro, Dagoberto; Lana-Peixoto, Marco Aurélio; Comini-Frota, Elizabeth Regina; Vasconcelos, Cláudia Cristina Ferreira; Sato, Douglas Kazutoshi; Ferreira, Maria Lúcia Brito; Parolin, Mçnica Koncke Fiuza; Damasceno, Alfredo; Grzesiuk, Anderson Kuntz; Muniz, André; Matta, André Palma da Cunha; Oliveira, Bianca Etelvina Santos de; Tauil, Carlos Bernardo; Maciel, Damacio Ramón Kaimen; Diniz, Denise Sisteroli; Corrêa, Eber Castro; Coronetti, Fernando; Jorge, Frederico M. H.; Sato, Henry Koiti; Gonçalves, Marcus Vinícius Magno; Sousa, Nise Alessandra de C.; Nascimento, Osvaldo J. M.; Gama, Paulo Diniz da; Domingues, Renan; Simm, Renata Faria; Thomaz, Rodrigo Barbosa; Morales, Rogério de Rizo; Dias, Ronaldo Maciel; Apóstolos-Pereira, Samira dos; Machado, Suzana Costa Nunes; Junqueira, Thiago de Faria; Becker, Jefferson (Arquivos de Neuro-Psiquiatria, 2018)
The expanding therapeutic arsenal in multiple sclerosis (MS) has allowed for more effective and personalized treatment, but the choice and management of disease-modifying therapies (DMTs) is becoming increasingly complex. In this context, experts from the Brazilian Committee on Treatment and Research in Multiple Sclerosis and the Neuroimmunology Scientific Department of the Brazilian Academy of Neurology have convened to establish this Brazilian Consensus for the Treatment of MS, based on their understanding that neurologists should be able to prescribe MS DMTs according to what is better for each patient, based on up-to-date evidence and practice. We herein propose practical recommendations for the treatment of MS, with the main focus on the choice and management of DMTs, as well as present a review of the scientific rationale supporting therapeutic strategies in MS.
Keywords: multiple sclerosis; drug therapy; consensus